Efektivitas Penggunaan Media Pembelajaran Fisika Berbasis Education Game pada Pembelajaran Fisika - Putri Lingga Harmita; Fatni Mufit (Navigation Physics : Journal of Physics Education, 2022)
As per most understudies, ideas in physical science are viewed as convoluted or hard to comprehend, causing understudy learning results to will quite often be low. To defeat this, the utilization of learning sight and sound as instructive games (instructive games) which have started to be applied to material science learning is thought of as adequate to assist understudies with grasping the idea of physical science, and learning media as instructive games are more alluring to understudies. This study means to decide the adequacy of involving this instructive game-based learning media in physical science learning, both regarding grasping ideas and learning results. The strategy utilized in this study utilizes a library research technique or approach. The type of this exploration is a writing study, with subjective information handling. The information assortment strategy utilized is through an efficient hunt that is applied from two data sets (Google Researcher and Sinta) with report examination to distinguish important writing studies. In light of the aftereffects of the primer review led, it was observed that game-based learning media were great. Understudies who utilize instructive games all the more effectively grasp different physical science ideas. Educators are made simpler in learning with game-based learning media that are fascinating and as per learning materials and learning is more alluring to understudies and ready to further develop understudy learning results.